The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/bfj-03-2019-0197
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of food obtained from olive by-products

Abstract: Purpose The purpose of this paper is to evaluate the market potential of food obtained from olive by-products. The marketing of such by-products (e.g. olive leaves and pulp) is a challenging opportunity for the sustainable development of the sector. Yet, consumer demand is still poorly understood. The paper contributes to filling the knowledge gap with an empirical survey of a sample of Italian consumers. Design/methodology/approach The authors provide an assessment of consumers’ willingness to accept (WTA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…Respondents were given a short, four-section questionnaire. Section 1 collected the demographic information, Section 2 assessed the respondent's attitudes toward the covariates of interest (organic food and food origin), Section 3 investigated the respondent's technophobia [29,30], and Section 4 asked the respondent's willingness to try food obtained from by-products [33]. Descriptive statistics of the sample and the questionnaire are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Respondents were given a short, four-section questionnaire. Section 1 collected the demographic information, Section 2 assessed the respondent's attitudes toward the covariates of interest (organic food and food origin), Section 3 investigated the respondent's technophobia [29,30], and Section 4 asked the respondent's willingness to try food obtained from by-products [33]. Descriptive statistics of the sample and the questionnaire are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Food technophobia (or food technology neophobia) is defined as consumers' fear, dislike, or avoidance of novel food technology [29]. Perito et al [33] found that it is a key driver limiting consumer acceptance of food with olive by-products. As a consequence, we included it as a control variable in our empirical investigation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, consumers' willingness to accept foods produced with olive by-product ingredients depends on the perception of different factors, mainly related to the general attitude of the consumer, rather than a product-specific choice. Indeed, information about the characteristics of olive by-products and the perception of the benefits from sustainable consumption can possibly offset the consumers' choice with a positive association between the use of vegetable by-products and sustainable production and environmental responsibility [8].…”
Section: Introductionmentioning
confidence: 99%